Impact of online cooperative learning strategies on self-directed learning among pre-service teachers - Chakyarkandiyil, Nisha; Prakasha, G. S. (Intelektual Pustaka Media Utama, 2025)
Self-directed learning (SDL) often drives learners to engage with what they want to learn. Thus, investigating teaching-learning strategies that drive SDL gains importance in this technology-driven era. The present study investigates the impact of online cooperative learning (OCL) strategies on SDL skills among pre-service teachers (PST). The study engaged 130 PSTs using a quasi-experimental non-equivalent control group design with a pretest and posttest. The study divided PST into a control group and an experimental group. The experimental group underwent OCL strategy, and the control group had a traditional online lecture method. The researchers measured the SDL of PST using the SDL scale. The paired sample t-test results indicated a significant enhancement in SDL skills among the experimental group compared to the control group. The findings underscore the importance of integrating cooperative learning (CL) strategies in online instruction to foster SDL ability among learners. Further studies may create user-friendly features in video-conferencing platforms that provide more opportunities to engage students with CL pedagogies.